Detection of Mycobacterium tuberculosis (MTB) in Fecal Specimens From Adults Diagnosed With Pulmonary Tuberculosis Using the Xpert MTB/Rifampicin Test. (22nd May 2015) - Kokuto, Hiroyuki; Sasaki, Yuka; Yoshimatsu, Shoji; Mizuno, Kazue; Yi, Lina; Mitarai, Satoshi
Abstract : We performed a proof-of-concept study using the Xpert MTB/RIF test for the detection of Mycobacterium tuberculosis from fecal samples. The overall sensitivity was 85.7% (95% CI; 73.8 – 93.6%) and the specificity was 100% (95% CI; 86.2–100). Abstract: Background.  The Xpert Mycobacterium tuberculosis (MTB)/rifampicin (RIF) is a fully automated diagnostic test that allows for the detection of MTB including its RIF resistance. Although the test is used for the diagnosis of tuberculosis (TB) in sputum samples worldwide, studies using fecal specimens are scarce. We therefore evaluated the efficacy of the Xpert MTB/RIF test for detection of MTB in fecal specimens obtained from adult pulmonary TB patients, confirmed by culture and/or molecular diagnostic methods. Methods.  We conducted a retrospective case-control study to provide proof-of-concept regarding the efficacy of the Xpert MTB/RIF test using fecal samples for diagnosing pulmonary TB via detection of MTB in adult patients (≥20 years) at the Fukujuji Hospital in Tokyo, Japan. Results.  Fecal specimens were obtained from 56 active pulmonary TB patients (including 48 sputum smear-positive and 8 sputum smear-negative patients), 10 non-TB patients (including 4 Myocobacterium avium complex infections), and 27 healthy individuals who were exposed to active pulmonary TB patients. The sensitivity of the fecal Xpert MTB/RIF was 100% (81.7%–100%) for detection of MTB in specimens from sputum smear-positive (1+ to 3+) patients, 81.0% (58.1%–94.6%) in specimens from sputum smear scanty positive patients, and 50.0% (15.7%–84.3%) in specimens from sputum smear-negative patients. Meanwhile, each of the fecal specimens from the non-TB group was negative for MTB (specificity 100%; 95% confidence interval, 86.2–100). Conclusions.  The fecal Xpert MTB/RIF test could detect MTB in a large proportion of smear-positive pulmonary TB patients, without frequent false-positive results at a TB referral hospital in Japan.